Validity and Reliability of the Global Warming Instrument: A Pilot Study Using Rasch Model Analysis - Amiruddin, Mohd Zaidi Bin; Samsudin, Achmad; Suhandi, Andi; Kaniawati, Ida; Costu, Bayram; Aminuddin, Adam Hadiana; Kuniawan, Fatah (Jurnal Pendidikan MIPA, 2023)
Abstract: This research aims to determine the profile of students regarding literacy skills for global warming material. This research uses a quantitative descriptive method to reveal the results of the research obtained based on students' responses to the 10 questions developed. This research was conducted at a school in Surabaya with a total of 15 respondents consisting of 4 men and 11 women. The results obtained were then analyzed using the Rasch Model with Winstep software to make it easier to map the level of instrument validity and the level of students' literacy skills. The results of this research reveal that the relationship between the instrument developed and students has very poor validity and reliability values with a value obtained of 0.22. However, the results of further analysis can map item difficulty levels and students' ability levels based on the Wright Map where students who have very high literacy skills are coded 01LK and 08PK while the most difficult item is Q2. Apart from that, students who have very poor literacy skills are good at coding 07LK while the easiest item is with code Q1. In this way, there is a need to improve problem instruments and further research to continue to develop the potential of scientific literature, not only on global warming material. Keywords: instruments, literacy scientific, measurements, rasch model. Abstrak: Penelitian ini bertujuan untuk mengetahui profil siswa mengenai kemampuan literasi untuk materi pemanasan global. Penelitian ini menggunakan metode deskriptif kuantitatif untuk mengungkap hasil penelitian yang diperoleh berdasarkan respon siswa terhadap 10 pertanyaan yang dikembangkan. Penelitian ini dilakukan di salah satu sekolah di Surabaya dengan jumlah responden sebanyak 15 orang yang terdiri dari 4 laki-laki dan 11 perempuan. Hasil yang diperoleh kemudian dianalisis menggunakan Rasch Model dengan software Winstep untuk memudahkan dalam memetakan tingkat validitas instrumen dan tingkat kemampuan literasi siswa. Hasil dari penelitian ini mengungkapkan bahwa hubungan antara instrumen yang dikembangkan dengan siswa memiliki nilai validitas dan reliabilitas yang sangat buruk dengan nilai yang diperoleh sebesar 0,22. Namun, hasil analisis lebih lanjut dapat memetakan tingkat kesulitan butir soal dan tingkat kemampuan siswa berdasarkan Wright Map dimana siswa yang memiliki kemampuan literasi sangat tinggi diberi kode 01LK dan 08PK sedangkan butir soal yang paling sulit adalah Q2. Selain itu, siswa yang memiliki kemampuan literasi yang sangat kurang baik diberi kode 07LK sedangkan butir soal yang paling mudah diberi kode Q1. Dengan demikian, perlu adanya perbaikan instrumen soal dan penelitian lebih lanjut untuk terus mengembangkan potensi literatur ilmiah, tidak hanya pada materi pemanasan global.  Kata kunci: instrumen, literasi sains, pengukuran, model rasch. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp912-922